New Vector of Development of Modern Ukrainian Dialectology - Beley, Oleg (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
Review “Hutsul dialect vocabulary and phrasemics in the Ukrainian literary language“. Dictionary : In 2 volumes / Editor-in-Chief :Vasyl Hreshchuk. Ivano-Frankivsk: Misto NV, 1, 2019, 584 p. Hutsul dialect vocabulary and phrasemics in the Ukrainian literary language. Dictionary : In 2 volumes / Editor-in-Chief: Vasyl Hreshchuk. Ivano-Frankivsk: Misto NV, 2, 2020, 468 p.